2018
DOI: 10.1093/jnci/djx286
|View full text |Cite
|
Sign up to set email alerts
|

Overall and Central Obesity and Risk of Lung Cancer: A Pooled Analysis

Abstract: The inverse BMI-lung cancer association is not entirely due to smoking and reverse causation. Central obesity, particularly concurrent with low BMI, may help identify high-risk populations for lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
96
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 42 publications
18
96
3
Order By: Relevance
“…The RR for BMI from observational studies were extracted from the World Cancer Research Fund (WCRF) Third Expert Report, except for lung cancer which used a large pooled analysis. 21,22 MR confirms and refines the causal effect of BMI on six obesity-related cancers For six out of seven evaluated cancer sites that were previously identified as being positively associated with BMI in the WCRF report, we also observed risk increases based on the MR analysis ( Figure 2). However, for each of these six cancer sites, the MR estimate for a 5-unit increment in BMI was notably higher than the WCRF estimate, being approximately 2-fold higher for cancers of the kidney [e.g.…”
Section: Methodssupporting
confidence: 82%
“…The RR for BMI from observational studies were extracted from the World Cancer Research Fund (WCRF) Third Expert Report, except for lung cancer which used a large pooled analysis. 21,22 MR confirms and refines the causal effect of BMI on six obesity-related cancers For six out of seven evaluated cancer sites that were previously identified as being positively associated with BMI in the WCRF report, we also observed risk increases based on the MR analysis ( Figure 2). However, for each of these six cancer sites, the MR estimate for a 5-unit increment in BMI was notably higher than the WCRF estimate, being approximately 2-fold higher for cancers of the kidney [e.g.…”
Section: Methodssupporting
confidence: 82%
“…BMI is crude measure of obesity, and other more accurate measures (eg, waist circumference, adipokines and so on) are required to fully explore the relationship between obesity, inflammation and the microbiome in development of CRC. An exemplar of this relationship is demonstrated for lung cancer, wherein the use of BMI demonstrates that a lower risk of lung cancer is associated with higher BMI but use of waist circumference or waist to hip ratio demonstrates and increased risk of lung cancer 51. Thus, this study sets the stage for future research to consider adding measures of adiposity beyond BMI when studying the aetiology and risk of CRC as well as other cancers influenced by obesity.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have attempted to use NHANES self-reported and measured weight data to generate corrections for BRFSS self-reported weight and height data (11,12,15) or for NHIS data (12,17,18,30), as well as for other data sets (31,32). However, the differences between the self-reported data in NHANES and the self-reported data in NHIS and BRFSS suggest that such corrections may not be completely accurate.…”
Section: Discussionmentioning
confidence: 99%